Violent death in the lives of police officers in Ghana; An evidence-based study - Bawah, Alhassan Salifu; Braimah, Awaisu Imurana (International Journal of Scientific Research and Management (IJSRM), 2019)
This article examines the recurrent and widespread spate of civilian attacks on police personnel in Ghana. It is an undeniable fact that police actions and inactions has led to civilian injuries and deaths in Ghana. Extensive media reportage on these incidences of police militarization and brutalities has painted the police service, albeit negatively, as an institution acknowledged for inflicting pain, torture, injury and killing of civilians at the least provocation. This perception has broken down police-community relations, which is one of the core mechanisms in crime detection and prevention in modern policing. Violent attacks on police personnel by a section of the Ghanaian public leading to injuries and in some extreme cases death, appears institutionalized.As a result, violent attacks on the police is not  perceived as an issue, either because of the quietism of the police administration itself, or it could be that the media perceive these unprovoked attacks on the police, as part of the occupational hazards and/or a fitting retribution for the police. In either way, the lives of police officers matter, just as the lives of the citizens they are mandated by law to protect. This study thematically focused on the changing trend of violent deaths in the lives of police officers killed in the line of duty by civilian assailants or criminal elements within the Ghanaian society. The paper argues that violent deaths and injuries caused to police officers have not been given the needed attention due to the ongoing antagonistic relationship between the police administration and the general Ghanaian public.